The Relationship between Food Taste, Food Appearance and Food Variety with Food Leftovers from a Normal Diet in Abdoel Moeis Samarinda Hospital - Humaira Azzahra; Rieska Indah Mulyani; Eka Farpina (PT FORMOSA CENDEKIA GLOBAL, 2023)
One of the goals of organizing food in hospitals is to provide quality food in order to achieve good nutritional status. To achieve this goal, Minimum Service Standards (SPM) indicators are needed. The aim of this research was to determine the relationship between food taste, food appearance and food variety with food waste from a regular diet at RSUD Abdoel Moeis Hospital, Samarinda. The research design is cross sectional with the Spearman statistical test to test the relationship between variables. There was no relationship between food taste, food appearance (p=0.504), food variety (p=0.337) with food waste from inpatients at Inche Abdoel Moeis Hospital, Samarinda. Meanwhile, the proposed policy refers to the Evaluation of Patient Meal Service Satisfaction at Inche Abdoel Moeis Hospital Samarinda based on the level of satisfaction which is still low, namely regarding food temperature with a percentage of 26.3%. The results of research at the Inche Abdoel Moeis Hospital in Samarinda showed that the average rating was good in terms of food taste, food appearance and food variety.